2012
DOI: 10.1111/j.1465-3362.2012.00513.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of training and delivering alcohol brief intervention on the knowledge and attitudes of community pharmacists: A before and after study

Abstract: This confirmed findings of previous studies that pharmacists unfamiliar with brief intervention could be trained to deliver this service. Pharmacists with positive attitude towards drinkers delivered a greater number of alcohol interventions and experienced increased work satisfaction than those pharmacists with less positive attitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…There is increasing evidence to support the effectiveness of community pharmacist delivery of health care advice, customer screening and brief intervention in reducing the incidence of obesity, smoking, hazardous/harmful problem drinking and drug overdose (Fitzgerald, Watson, McCaig, & Stewart, 2009;Dhital, Whittlesea, Norman, & M, 2010;Krska & Mackridge, 2014;Saba, Diep, Saini, & Dhippayom, 2014;Sheridan et al, 2008;Sheridan, Stewart, Smart, & McCormick, 2012;Shimane, Matsumoto, & Wada, 2014;Todd et al, 2014;Watson & Blenkinsopp, 2009) and warrants expansion to include specific misuse of OTC codeine . Pharmacist and counter staff training programmes in the delivery of brief interventions in the area of substance misuse and mental health are reported to remedy lack of staff knowledge or confidence and result in increased knowledge, positive attitudinal scores, work satisfaction and self-related competencies (Butler & Sheridan, 2010;Dhital, Whittlesea, Milligan, Khan, & Norman, 2013;Fitzgerald et al, 2009;McBride, Pates, Ramadan, & McGowan, 2003;Sheridan et al, 2008). Strategies to improve pharmacist counseling and enhance customer engagement in health care advice, screening and brief intervention processes are warranted (Puspitasari, Aslani, & Krass, 2010).…”
Section: Codeine Focused Interventionsmentioning
confidence: 95%
“…There is increasing evidence to support the effectiveness of community pharmacist delivery of health care advice, customer screening and brief intervention in reducing the incidence of obesity, smoking, hazardous/harmful problem drinking and drug overdose (Fitzgerald, Watson, McCaig, & Stewart, 2009;Dhital, Whittlesea, Norman, & M, 2010;Krska & Mackridge, 2014;Saba, Diep, Saini, & Dhippayom, 2014;Sheridan et al, 2008;Sheridan, Stewart, Smart, & McCormick, 2012;Shimane, Matsumoto, & Wada, 2014;Todd et al, 2014;Watson & Blenkinsopp, 2009) and warrants expansion to include specific misuse of OTC codeine . Pharmacist and counter staff training programmes in the delivery of brief interventions in the area of substance misuse and mental health are reported to remedy lack of staff knowledge or confidence and result in increased knowledge, positive attitudinal scores, work satisfaction and self-related competencies (Butler & Sheridan, 2010;Dhital, Whittlesea, Milligan, Khan, & Norman, 2013;Fitzgerald et al, 2009;McBride, Pates, Ramadan, & McGowan, 2003;Sheridan et al, 2008). Strategies to improve pharmacist counseling and enhance customer engagement in health care advice, screening and brief intervention processes are warranted (Puspitasari, Aslani, & Krass, 2010).…”
Section: Codeine Focused Interventionsmentioning
confidence: 95%
“…The current literature indicates that providing pharmacy staff training in the delivery of targeted substance misuse screening and brief interventions show promise in addressing staff knowledge, attitudes, skills and competencies in counselling and patient consultations (McBride, Pates et al 2003;Sheridan, Wheeler et al 2008;Fitzgerald, Watson et al 2009;Butler and Sheridan 2010;Dhital, Whittlesea et al 2013). Given the difficulties involved in engaging with difficult customers, recommendations have included increased practice based emphasis on pharmacist and technician training in the area of addiction and communication skills (Butler and Sheridan 2010;Cooper 2011;Cooper 2013b;Hamer, Spark et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We conservatively estimated that approximately 6032 pharmacy customers would need to be approached and invited to participate, for 2473 to agree to be screened. Based on findings from previous feasibility studies [11,15,20] we expect approximately 44% ( N  = 1088) to be identified as risky drinkers with the Single Alcohol Screening Question (SASQ; see below) preliminary screen. We estimate that 50% (N  = 544 ) of those who screen positive will consent to participate in the study and that 25% ( N =136) of these will be found not to be eligible when the AUDIT is administered in the second stage of the procedure.…”
Section: Methods and Designmentioning
confidence: 99%
“…Guided by the Medical Research Council (MRC) framework for developing and evaluating complex interventions [9], the design of this trial has been informed by our previous studies assessing pharmacy customers’ perceptions and the feasibility of BI in community pharmacies [10,11] and studies that recommend establishing the acceptability of discussing alcohol use in health care settings [12]. Our NHS Westminster study which assessed 102 pharmacy customers perceptions of BI established that most customers ( N  = 97, 96%) would find it acceptable to discuss their drinking with the pharmacist [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation